Evaluation of Financial Performance of Urban Local Bodies in Haryana: A Case Study of Municipal Council of Bahadurgarh (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The study describes to the emerging trend of Municipal Finance. In this study also made an attempt to analyze the financial position of Bahadurgarh municipal Council. Municipal’s Government has major problem of gap between obligation and their responsibility. The objectives of the present study are, to analyze the revenue& expenditure pattern and trends of Municipal Council of Bahadurgarh and second objective is, to examine the financial position of Municipal Council of Bahadurgarh.The present study is based on secondary data. Annual data for the time period from 2003-04 to 2013-14 has been used in the analysis. It is collected from the various sources such as annual budget report of Municipal Council of Bahadurgarh, Haryana Statistical Abstract Affairs book and other Government Publications.Analyzing the data and it was found from the study that the financial position of Municipal Council of Bahadurgarh is excellent. The total revenue increased from INR 6.86 in 2003-04 to INR 24.09 and total expenditure increased from INR 3.12 crore in 2003-04 to INR 21.59 crore in 2013-14, but it increased with high fluctuation during concerned study time period